Assessement of Rhesus factor awareness and knowledge among women in Imo State Nigeria - Ojiakor-Umenze, Ifeoma; Innocent, H., Kasarachi; Nwaozor, A., Onyekachi; Aluka, N., Cynthia (COMMICAST, 2024)
Despite the considerable influence of Rhesus factor incompatibility on maternal and fetal health outcomes, little is known about women's awareness and knowledge of the Rhesus factor in Imo State, Nigeria. This study aimed at assessing the levels of awareness and knowledge of the Rhesus factor among women in Imo state. The researchers sought to determine the extent to which health institutions' communication strategies contribute to women's understanding and awareness of Rh factor, to ascertain the knowledge level of Rh factor and its implications in pregnancy among women in Imo State. With a theoretical framework built on the Health Belief Model, the study surveyed a sample of 385 respondents (per Wimmer and Dominick online sample size calculator), drawn from a population of 2,688,605. The instrument for data collection was a structured questionnaire which was administered via a multi-stage sampling technique. The key findings showed that the though the level awareness of the Rhesus factor among the women in the State was high, the knowledge level of the specificity of the Rh compatibility issues on maternal and child health and its implications in pregnancy was low. The findings also correlate the low knowledge level with the nature of communication strategies employed by healthcare institutions and professionals in the State to diffuse information on the Rhesus factor among the women. The researchers therefore recommend as follows Health institutions and professionals should include Rhesus factor education for women during antenatal care; the State Ministry of Health should embark on awareness campaigns in the rural areas using society-specific communication strategies to improve knowledge of the Rh factor; Rhesus Factor education should be included in reproductive health education programmes for girls and young ladies.